Landlord versus tenants: a critical appraisal of conflict in tenancy law in Nigeria (2017)
In Nigeria today, housing; particularly in the urban areas remains an intractable problem. Acute shortage of shelter is a common phenomenon as many people are chasing the few available accommodation. In recent times, the problem of shelter in Nigeria has reached a threatening stage with different fallouts ranging from socio-economic to legal and cultural impacts. The two major stakeholders in tenancy contract, namely: (i) Landlord and (ii) Tenant, now have their relationship regulated by plethora of tenancy laws in Nigeria. This paper examines the duties and liabilities of landlord and tenant under the common law and diverse existing tenancy laws in Nigeria. Critical issues such as types of tenancy, commencement of tenancy relationship and the legal procedure for terminating such relationships were carefully examined. It is observed that oftentimes there are conflicts between the landlords and tenants which attempts have been made by drafters of the law to either prevent or legally resolved. It is however the opinion of this writer that such tenancy laws should be reviewed to consider and accommodate other issues such as economic and sociological factors as legal consideration without more can neither prevent nor resolves conflict arising out of tenancy relationships.